Mixed Composting of Palm Oil Empty Fruit Bunch (EFB) and Palm Oil Mill Effluent (POME) with Various Organics: An Analysis on Final Macronutrient Content and Physical Properties - Hau, L.J. (Springer Science+Business Media B.V., 2020)
Abstract: Large amounts of palm oil consumption in Malaysia leads to large amounts of by-products such as Empty Fruit Bunch (EFB) and Palm Oil Mill Effluent (POME) requiring disposal. Limited treatment methods for these waste products has resulted in interest to use EFB + POME in composting when mixed with different biomass sources for nutrient enhancement. This work is aimed at enhancing the final macronutrient content and physical properties of EFB:POME based fertilizers using various organic waste products as additives to achieve specific initial C/N values. Seven batches of compost were prepared, Compost A (EFB and POME in 1:1 weight ratio); B (fishmeal); C (bonemeal); D (bunch ash) and mixed compost of 1:1 EFB:POME, fishmeal, bonemeal, bunch ash and sawdust in different composition to obtain initial C/N ratios of 35 (E), 42 (F) and 47 (G). The results indicated the composts achieved maturation on day 40 based on stable pH profiles from day 40 to 52. The C/N ratio of the mixed Composts E, F and G were reduced from 35 to 16, 42 to 15 and 47 to 22 respectively. The mixed composts had a porous structure which supports aeration and a high mass yield of 88 to 90 with a maturation moisture content of 55â70. The final C/N ratios of Compost E and F was lower than 20 which was an indication of maturation, while the C/N of Compost G was slightly above 20 (22.3). All three batches of EFB mixed composts experienced an increase in Nitrogen (+ 18 to 62), Phosphorus (+ 125 to 906) and Potassium (+ 262 to 294) which indicates that blending EFB:POME based fertilizer with various organic waste can improve the physical properties and nutrient quality. Graphic Abstract: Figure not available: see fulltext.. Â© 2020, Springer Nature B.V.